If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3r + 6) = 21 Reorder the terms: 7(6 + 3r) = 21 (6 * 7 + 3r * 7) = 21 (42 + 21r) = 21 Solving 42 + 21r = 21 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 21r = 21 + -42 Combine like terms: 42 + -42 = 0 0 + 21r = 21 + -42 21r = 21 + -42 Combine like terms: 21 + -42 = -21 21r = -21 Divide each side by '21'. r = -1 Simplifying r = -1
| 60=6(6m-7)-6 | | -4(3n-4)=-56 | | -25=-1-6(1+3x) | | k^3=144k | | -7(1+3p)=-70 | | 10x^2+40x+2=0 | | 8x^3+64=0 | | 3(2n+4)+5(3-2n)=7-2n | | -2=-7(4a+7) | | 3(2+5x)=-39 | | 6(8k+8)=0 | | 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 | | 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 |